2000
DOI: 10.7227/ijmee.28.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Notation of Planetary Gear Trains by Canonical Number Approach (Max Code)

Abstract: In the present work, the concept of 'Max Code' approach is used for establishing identification code of planetary gear spur trains. Such a representation provides an expression rather than an unique number. An attempt is made here to establish these expressions for distinct single and two degrees of freedom planetary gear trains. The concept of maximum code (Max Code), as a canonical number is to introduce a symbolic notation for describing two degrees of freedom spur planetary gear trains with the configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Chatterjee and Tsai [8] compared some conventional graph representation and used basic kinematic units to combine planetary mechanisms. Other synthetic methods includes: max code [9] , kinematic fractionation [10][11][12] , graph theory based on loops [13][14] , genetic algorithm [15] , simplified structural graph and structural chain graph [16] , kinematic chain graph [17] , etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chatterjee and Tsai [8] compared some conventional graph representation and used basic kinematic units to combine planetary mechanisms. Other synthetic methods includes: max code [9] , kinematic fractionation [10][11][12] , graph theory based on loops [13][14] , genetic algorithm [15] , simplified structural graph and structural chain graph [16] , kinematic chain graph [17] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…References [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], which are associated with the characteristic of gear trains (e.g. the characteristic of the structural components, kinetic characteristics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…But they contain less the characteristics of the integral structure of planetary mechanisms. On the other hand, general synthesis methods about PGTs are: structural graph and chain [1], innovated synthetic method based on kinematic chain [4], graph based on the description of kinematic characteristics [5], canonical number [6], topological graph by using kinematic fractionation [7][8][9], the graphic means using loops [10][11], etc. In reference [4], An Peiwen and Huang Maolin put forward the structural principle and synthesis corresponding method; they also found that PGTs can be obtained by the evolvement of single and compound chains.…”
Section: Introductionmentioning
confidence: 99%